Risk Factors of Neonatal Sepsis and Its Association with Clinical Profile (The Planet, 2023)
Background: Sepsis is a leading cause of neonatal mortalityglobally, including in Bangladesh. Neonatal sepsis is asignificant public health issue, especially in underdevelopednations, where it is a primary cause of neonatal mortalityand morbidity. Objective: The main objective of this studywas to identify the risk factors of neonatal sepsis and itsassociation with clinical profile. Method: This CrossSectional study was conducted at a medical college andhospital in Sylhet, including 80 neonates who were admittedto the neonatal unit and suspected of having neonatal sepsis.Sepsis diagnosis was based on clinical features. The clinicalfeatures assessed were fever (≥38.0°C), hypothermia(≤36.5°C), convulsions, lethargy, poor feeding, respiratorydistress, vomiting, bulging. Results: Females accounted forthe majority (76.25%) of cases, with 50% of cases occurringwithin the 15–22-day timeframe. 86.1% of cases exhibited inadequate hygiene, with 58.2%displaying suboptimal cord care, 26.3% being formula-fed, and 25% utilizing bottles. Coughwas present in 47.7% of cases, while cough with respiratory distress was present in 68% ofcases. Fever was present in 83.5% of cases, decreased urine output in 38%, convulsion in17.7%, and jaundice in 16.3%. Poor hygiene and cough with respiratory distress had thehighest odds ratio of 4.147. 50% received antibiotics for 1-5 days and 58% were hospitalized for 6-10 days. Conclusion: Newborn sepsis is more common in neonates admitted to NICUsin public hospitals in Bangladesh. Our findings indicate that fever and respiratory distress arecommon clinical characteristics of sepsis in infants.
Keywords: Neonatal sepsis; poor hygiene; mode of discharge